Preventing Cyber ​​Threats Early: Cyber ​​Crime Education for Students of SMKN 1 Katapang - Aisah Nur Endah Sari; Solehhudin Solehhudin; Irwan Ardhiyanto; Vicky Muhammad A; Nabila Sri Gustina; Afifah Afifah; Muhamad Zaki; Ilham Hidayat; Andika Fazri F; Ari Ardiansyah; Regi Muhammad S (Jurnal Pengabdian Masyarakat: Bisnis dan Iptek (JPMBISTEK), 2024)
The community service team, comprising faculty and students, implemented initiatives to raise awareness about the rapid advancement of digital technology, which facilitates access to information, communication, and everyday tasks.  Nevertheless, in conjunction with these conveniences, numerous cybercrime concerns have emerged, including phishing, hacking, cyberbullying, and the theft of personal data.  The deficiency in awareness and understanding of these concerns, especially among students, underpins our community service activity.  The events consisted of interactive outreach directed at 11th-grade students in the RPL program at SMKN 1 Katapang—the employed procedures comprised pre-tests, material presentations, phishing web simulations, conversations, and post-tests.  The subjects addressed encompassed categories of cybercrime, its adverse effects, and preventive strategies employing security technology such as firewalls, two-factor authentication (2FA), and SSL.  The findings indicated significant enthusiasm among participants and an enhanced comprehension of digital hazards and the significance of personal data protection.  This effort demonstrates that early education on cybercrime is essential for cultivating a prudent and secure generation in the responsible use of digital technology.